EFFECTIVE EDUCATION ABOUT HEALING TO MANAGE STRESS PENDIDIKAN KEFEKTIFAN TENTANG HEALING UNTUK MENANGANI STRES - Nur Amsyiah R Djunaidi; Frezy Paputungan; Ade Yul Pascasari (Jurnal Ilmu Pendidikan dan Budaya, 2023)
The emergence of this self-healing phenomenon attracted a lot of attention from generation Zduring the pandemic, starting in 2021 until now. According to (Madura, 2021) self-healing meansself-healing, in other words healing means "a process of cure" a process of treatment or healing. Crane(in Aisa et al., 2021) explains that self-healing is a process of treatment or healing carried out byoneself through the beliefs one has and is supported by the environment and external supportingfactors. Meanwhile, in practice, self-healing has a term that uses the process principle that the humanbody is actually something that can scientifically repair and heal itself in certain ways (Bahrien &Ardianty, 2017). The successful implementation of self-healing depends on self-confidence andinternal communication, which means there is a need for the desire and ability to carry out internaldialogue. Self-healing is useful for recognizing and understanding emotions (Mutoharoh, 2022).Self-control also helps identify problems that individuals are experiencing, thought patterns, and otherpsychological aspects that influence current conditions. Sari & Aryanto (2022) say that Self-Healingis a method of healing disease not with the help of drugs, but by eliminating feelings of anxiety andemotional outbursts that are hidden in the body. Self-healing is usually done because students areexperiencing academic stress. The consequences of academic stress occur in the school environmentor educational environment.According to Desmita (in Barseli & Nikmarijal, 2017) academic stressors are defined as stressexperienced by students due to learning or problems related to learning activities; such as pressure toimprove grades, long periods of studying, cheating, lots of assignments, exam results, makingimportant decisions, exam difficulties, and stress management. Rahmawati (in Barseli et al., 2017)states that there are several factors that cause stress in students; including excessive academicdemands, poor exam results, mounting homework, and the social environment. Academic stressoccurs when expectations of academic achievement from parents, teachers, and peers increase. Theseexpectations often do not match students' abilities, causing psychological pressure that affects learningat school (Barseli & Nikmarijal, 2017).